ALAT PENqERING (P.ENIRIS) Alat Pengering (Peniris) Sistem Vakum pada Gorengan Ceriping Ubi SISTEM VAKUM PADA GORENGAN CERIPING ABSTRACT gets UBI, PENGHEMAT UNTUK INDUSTRI PEMAKAIAN MIN’AX-CONNNC KECIL PEDESAAN - Said, Soeprapto Rachmad (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
The cassava chip industry "Berkah’", in producing difficuities especially in iastening the chips as the products, often the marketing delivery. Having been fried, the ciqssava chips are to firstly be dried wiih conventional*system 48 hours for serondok the chips’still snack, then they are made in plastic packages. take number of oil with them so that the product moldy though they are already in the packages. for more than 24 hours and The problem is that can be easily rancid and It ls difficult to make the oiiin the chips out and efforts taken may cost,much so that it is hard fl’, th; ,;;ii:;;;il;,rrtry to har" such an act’ Considering problem all the aspects revealecl by means of voucher progrurrr, chips frying. above, the servants wish to solve the to rnake a vakum system drayer for cassava The method used is making a vacuum system dryer within the specification follows: (i) the vacuum system ary., is a cylinier tuue;,(z)it consists of’two tubes; (3) the lower tube is used to store the crrips goi.rg to be driei and the upper one functions as the sucker; (4) the diameter_and the high of the lower tube are 450 mm and 750 mm, and that of the upper one are 450 mm unJqso mm; (5)-ii i, pru."J;rh;;;p"i piayed with i850 rpm by means of electric motor %Hp; (6) the upper tube can be moved for 180 degree by using switch placed to be dried are put into the tube, then air is given t,rb" u fun to the rroia"r. The chips, which are going and absorbing in done through pone of the tip of the tube. The oil will be absoibed in two ways, by means of pressure differences and air flow making the ojl out of the chips. The results of this practice hours; (2) the oil succeeded are to be standing-p^ut position are as follows: (r) ti ary serondok to’chase snack, it is required 2 in one process is ibout 50 to 60 cc; (3) the snacks i1 the tube; (4)time required ro. ur.*ging the snacks’in is about 20 m.inutes; (5) having *oik.d for 2-hours, the machine should be stopped; (6) the erectricitv the capacitv approximately .*"0 io. th" z hou* is for utout’ii j:g;" of 1.5 kg; (g) time required 45 menutes, and thi oil gained for drying ubr;l kg drying the cassava chips is % hours is i x 0,g Kw dryrng process. Key words: r vacuum Iilill’fi:il,:T ffi;i,fl;n system dryer, cassava oari Fakultas e/3 standing riif; tie tube with of the ,rb;; ,ilo!’l; for"each pro."*. is 15 cc. The cost for " *:t ..i,7/Kwh: chips frying, and serondok reknik rrNY, sebagai Ketua Drs. Suprapto Rp 1g7 for each snack.